Introduzione al Vol. 2 "The representation of death in modern society" - Bifulco, Luca; Cavicchia Scalamonti, Antonio; Pecchinenda, Gianfranco; Santoro, Alessandra (Funes. Journal of narratives and social sciences, 2018)
Death represents one of those few experiences that every society throughout history faces. It has been defined as the marginal situation par excellence (Berger, 1969). Since it cannot be known concretely, it exists at the margins of every symbolic system, of any solid structure of meaning that a society can possess. Conceiving one’s own mortality and coping with the death of loved ones bears a threat to the typical way of understanding and defining the social world. The awareness of death is difficult to handle, since it sheds light on the whole existence of those who must cope with it. Therefore, every group as well as every individual, faced with the end of human life, the loss and the mourning process, must also ask oneself about the sense and the meaning of death in order to face its scope.